Eltrombopag with gemcitabine‐based chemotherapy in patients with advanced solid tumors: a randomized phase I study. (28th August 2014) - Winer, Eric S.; Safran, Howard; Karaszewska, Boguslawa; Richards, Donald A.; Hartner, Lee; Forget, Frederic; Ramlau, Rodryg; Kumar, Kirushna; Mayer, Bhabita; Johnson, Brendan M.; Messam, Conrad A.; Mostafa Kamel, Yasser
Abstract Preventing chemotherapy‐induced thrombocytopenia could avoid chemotherapy dose reductions and delays. The safety and maximum tolerated dose of eltrombopag, an oral thrombopoietin receptor agonist, with gemcitabine‐based therapy was evaluated. Patients with advanced solid tumors and platelets ≤300 × 109/L receiving gemcitabine plus cisplatin or carboplatin (Group A) or gemcitabine monotherapy (Group B) were randomized 3:1 to receive eltrombopag or placebo at a starting dose of 100 mg daily administered on days −5 to −1 and days 2–6 starting from cycle 2 of treatment. Nineteen patients (Group A, n = 9; Group B, n = 10) received eltrombopag 100 mg and seven (Group A, n = 3; Group B, n = 4) received matching placebo. Nine eltrombopag patients in Group A and eight in Group B had 38 and 54 occurrences of platelet counts ≥400 × 109/L, respectively. Mean platelet nadirs across cycles 2–6 were 115 × 109/L and 143 × 109/L for eltrombopag‐treated patients versus 53 × 109/L and 103 × 109/L for placebo‐treated patients in Groups A and B, respectively. No dose‐limiting toxicities were reported for eltrombopag; however, due to several occurrences of thrombocytosis, a decision was made not to dose‐escalate eltrombopag to >100 mg daily. In Groups A and B, 14% of eltrombopag versus 50% of placebo patients required chemotherapy dose reductions and/or delays for any reason across cycles 3–6. Eltrombopag 100 mg once daily administered 5 days before and after day 1 of chemotherapy was well tolerated with an acceptable safety profile, and will be further tested in a phase II trial. Fewer patients receiving eltrombopag required chemotherapy dose delays and/or reductions compared with those receiving placebo.